Optimalisasi Sosialisasi Penguatan Nilai – Nilai Pancasila dan Pembentukan Identitas Anak Muda Berbasis Kearifan Lokal di SMPN 17 Palangka Raya : Menekankan bahwa ini adalah pendekatan menyeluruh untuk pembentukan karakter di sekolah menengah - Firman, Firman; Hadibowo , Ronald; Joshua, William; Pransiska, Mila; Tania, Elsa; Sabeni, Aolia; Alwine, Alwine; Rahman, Abdul; Septiani, Septiani; Delima, Delima (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2026)
This study aims to analyze the effectiveness of the socialization of strengthening Pancasila values and its role in the formation of youth identity based on local wisdom at SMPN 17 Palangka Raya. The main background of this research is the issue of weakening understanding of the state ideology and the erosion of local cultural values among students. The research method used is descriptive qualitative with a case study approach. Data collection was carried out through participant observation, in-depth interviews with teachers, students, and community leaders, as well as analysis of relevant school program documents. The results show that the socialization of Pancasila values, when integrated with Dayak local wisdom (such as the Huma Betang concept which emphasizes togetherness, tolerance, and mutual cooperation), successfully creates a more contextual and relevant understanding for students. Effective strategies include intra-curricular learning through Pancasila and Citizenship Education (PPKn) subjects, as well as extracurricular activities involving the direct practice of local wisdom values. The formation of youth identity at SMPN 17 Palangka Raya is reinforced by a sense of pride in their own culture, as well as the ability to internalize the universal values of Pancasila. This strengthening not only enhances students' nationalism but also encourages attitudes of tolerance and mutual cooperation in daily life. The conclusion of this study is that the integration of Pancasila and local wisdom is an effective model in addressing identity challenges in the era of globalization, bridging national values with local cultural roots. Keywords: Pancasila, Youth Identity, Local Wisdom, SMPN 17 Palangka Raya, Huma Betang